Angular Dependence of the Total Cross Section in Inverse Compton Scattering (Theoretical study) - Sana Almabrouk Almahdi, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
Inverse Compton Scattering (ICS) of relativistic electrons with low-energy laser photons is a highly efficient mechanism for generating high-energy gamma rays. This study presents a theoretical calculation of the total cross section for ICS in head-on collisions, specifically investigating its dependence on the scattering angle (θ_s). The total cross section is a fundamental parameter for accurately estimating gamma-ray production rates and scattering probabilities. Our findings indicate that angular effects significantly influence the cross-sectional values. Results show that at high gamma-ray energies, the total cross section decreases, whereas at lower energies—corresponding to larger scattering angles—it approaches the classical Thomson scattering limit (σ_(Th≈)665mb). This transition confirms the consistency of the theoretical model across different energy regimes. Data from the SLEGS, Hayakawa, and LADON facilities were utilized to verify these angular dependencies. The results demonstrate an inverse relationship between the energy of the produced gamma rays and the scattering probability. These insights are crucial for optimizing ICS-based sources utilized in nuclear physics, medical imaging, and industrial applications, particularly in the transmutation of nuclear waste.
Keywords: Inverse Compton Scattering; total cross section; relativistic electrons; scattering angle; gamma rays